Diclofenac sodium and prednisolone acetate ophthalmic solution in controlling inflammation after cataract surgery (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):343-7.The abstract of this article is available on the PubMed website